2015
DOI: 10.15714/scandpsychol.2.e5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning after losing a close friend in an extreme terror incident

Abstract: Scandinavian Psychologist, 2(2015)e5http://dx.doi.org/10. 15714/scandpsychol.2.e5 This is an open access journal available at http://psykologisk.no/sp/ Articles can be deposited in the institutional repository provided its original source is cited clearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
8
0
2
Order By: Relevance
“…Our findings are only partly consistent with studies that have reported strong associations between trauma-related disorders, cognitive dysfunctions and a wide-range of physical and psycho-social dysfunctions, e.g. work-related problems (Johnsen, Laberg, Matthiessen, Dyregrov, & Dyregrov, 2015 ; Ogle et al, 2013 ; Sanderson & Andrews, 2006 ; Sandström et al, 2011 ; Wilson et al, 2006 ). Especially in settings of war and conflict, impairments in psycho-social functioning may aggravate poverty and lack of prospect.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings are only partly consistent with studies that have reported strong associations between trauma-related disorders, cognitive dysfunctions and a wide-range of physical and psycho-social dysfunctions, e.g. work-related problems (Johnsen, Laberg, Matthiessen, Dyregrov, & Dyregrov, 2015 ; Ogle et al, 2013 ; Sanderson & Andrews, 2006 ; Sandström et al, 2011 ; Wilson et al, 2006 ). Especially in settings of war and conflict, impairments in psycho-social functioning may aggravate poverty and lack of prospect.…”
Section: Discussionsupporting
confidence: 86%
“…The severity of the friends’ reactions is also evident when compared with the scores of bereaved parents and siblings after the killings at Utøya, where 19 months after the killings equal high scores were found among the friends, especially on complicated grief (K. Dyregrov, Dyregrov, & Kristensen, 2014; Johnsen et al., 2015). Servaty-Seib and Pistole (2006–2007) found in their study that adolescents experienced higher grief intensity for friends’ versus grandparents’ deaths.…”
Section: Discussionmentioning
confidence: 98%
“…The nature of girls’ relationships might also imply that they might be especially at risk for complicated reactions (Coleman, 2011; Malone, 2012). The risk factors are well documented for family members, but may also apply for bereaved friends (Johnsen et al., 2015). Prolonged grief disorder is a common form of complicated grief, characterized by marked and chronic separation distress (i.e., searching and longing for the deceased), loneliness, preoccupation with thoughts of the deceased, and traumatic distress such as feelings of disbelief, mistrust, anger, shock, detachment from others, and somatization (Prigerson et al., 1995; Stroebe, Schut, & Stroebe, 2007).…”
Section: Long-term Effects Of Loss and Traumamentioning
confidence: 99%
“…Vi har undersøkt etterlattes nivå av psykologisk stress og traume-og sorgreaksjoner etter terroren, for å se om, og eventuelt hvordan, det påvirker skoleprestasjoner, arbeidsfunksjon og sosialt liv (Dyregrov, Dyregrov & Kristensen 2014a;Dyregrov & Kristensen 2015;Johnsen, Laberg, Matthiesen, Dyregrov & Dyregrov 2015). Videre har vi studert hvilket offentlig hjelpetilbud etterlatte har fått, og om det tilfredsstiller føringene i den proaktive modellen og etterlattes behov for hjelp (Dyregrov, Kristensen & Johnsen 2014b).…”
Section: Innledningunclassified